Kajian terhadap Pelaksanaan Kebijakan Subsidi Minyak Goreng untuk Rumah Tangga Miskin di Kota Depok - PRIANTO, SIGIT INDRA (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
The subsidy program of cooking oil for underprivileged households in Depok Municipality consists of two liters cooking oil per each underprivileged household with subsidy value of IDR 2.500 per liter. This research is qualitative, descriptive, and interpretive. The purpose of this research is to describe the problems which emerged in the implementation stage of cooking oil subsidy program in Depok Municipality. The result of this research shows that Depok Municipality encountered disparity problem of subsidy allocation with the amount of underprivileged household targets. Moreover, the other problems included technical and managerial aspects which were faced by local government in Depok Municipality. These problems also influenced the effectiveness of the program implementation.